Elementos de interoperabilidade na catalogação descritiva: configurações contemporâneas para a modelagem de ambientes informacionais digitais - Castro, Fabiano Ferreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The intensive use of Information and Communication Technologies (ICT) generates the development of a various possibility of metadata standards, essential in environments manipulation of bibliographic data. Actualy, there is a tendency for the availability of resources and informational content in digital format and not use of appropriate standards to represent and describe these features, considered the subject of concern for the scientific community. The thesis shows that methodologies of Descriptive Cataloging and bibliographic description of an ontology is explicit in the code and metadata standards favor of retrieval information from the database modeling and construction of forms of representation of information resources, enabling interoperability in digital environments. This proposal verifies in the scientific literature the applicability and functionality of technologies and mechanisms that are available currently as the information descriptive treatment in digital informational environments. Objective is, as new scenarios of Descriptive Cataloging identify and analyze for the initiative MarcOnt, its similarities and differences regarding the MARC 21 metadata standard of the Librarianship area, in an attempt to compare and link them with tools that standardize and describe form and content aspects of bibliographic resources, knowledge components of Information Science. With a methodology exploratory and descriptive analysis of the subject, based on the Perspectivism (PETERSON, 1996) can be MarcOnt and an understanding of the technologies that are involved within the scope of digital libraries for building Semantic Web. As a result of this investigation is presented a proposal for modeling a functional requirements of digital informational environments that ensure interoperability in the... (Complete abstract click electronic access below)

O uso intensivo das Tecnologias da Informação e Comunicação (TIC) gera o desenvolvimento de uma gama de padrões de metadados, instrumentos fundamentais nos ambientes de manipulação de dados bibliográficos. Verifica-se, atualmente, uma tendência para a disponibilização de recursos e conteúdos informacionais em formato digital e a não utilização de padrões adequados para representar e descrever estes recursos, considerado alvo de preocupação da comunidade científica. A tese levantada indica que as metodologias da Catalogação Descritiva e uma ontologia para a descrição bibliográfica explicitada nos códigos e padrões de metadados favorecem a recuperação da informação, a partir da modelagem do banco de dados e da construção de formas de representação dos recursos informacionais, possibilitando a interoperabilidade em ambientes digitais. A proposta de pesquisa está pautada em verificar na literatura científica a aplicabilidade e a funcionalidade das tecnologias e dos instrumentos que estão disponíveis atualmente, para o tratamento descritivo das informações em ambientes informacionais digitais. Objetiva-se, a partir dos novos cenários da Catalogação Descritiva identificar e analisar a iniciativa MarcOnt, suas similaridades e diferenças com o padrão de metadados MARC 21, da área de Biblioteconomia, na tentativa de compará-los e articulá-los com as ferramentas para a padronização de descrição dos aspectos de forma e de conteúdo de recursos bibliográficos, componentes do conhecimento da Ciência da Informação. Com uma metodologia de análise exploratória e descritiva do tema, e fundamentada no Perspectivismo (PETERSON, 1996) será possível uma compreensão do MarcOnt e as tecnologias...
Keywords: Catalogação descritiva; Metadados; Ontologias (Recuperação da informação)